PROGRESIF AWARD BAGI KANIT RESERSE POLSEK PANCORAN MAS - Aliyth Prakarsa (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2009)
The increasing number of criminal cases involving police discretion has raised concerns regarding coercive law enforcement practices rooted in legal positivism. This article critically examines police discretion through the case of The Story of a Pair of Shoes to demonstrate that law enforcement should prioritize substantive justice rather than rigid legal formalism. Drawing on the perspectives of contemporary legal scholars, the study argues that discretionary authority must be exercised within the framework of humanity, proportionality, and the public interest. It concludes that a justice-oriented approach to police discretion is essential for strengthening public trust and enhancing the legitimacy of law enforcement institutions.